Installation of an online power quality monitoring system for the industry and applications - Boonseng, C.; Gitnumlapcharoen, P.; Boonseng, R. (My University, 2023)
The use of non-linear power loads causes power system distortion or harmonic problems. When that problem occurs, it must be resolved in time. Therefore, this document presents an online power quality measurement system that can quickly notify events and information. Fast data acquisition results in the quick analysis as well. Finally, the electrical system will be solved by installing a hybrid filter that is suitable for that problem.
Keywords: active power filter; harmonic; hybrid power filter; non-linear load; online measurement; passive power filter; power quality